Surgical Treatment of Spontaneous Pneumothorax: Pleural Abrasion or Pleurectomy? - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2019)
Purpose: A primary spontaneous pneumothorax is a condition that occurs predominantly in young and thin male individuals who do not have any history of underlying lung disease. Various techniques such as pleural abrasion and pleurectomy are used to reduce the recurrence rate, but there exists no consensus among surgeons on which surgical technique offers the lowest risk of recurrence. We aimed to compare the efficiency and recurrence risk of pleural abrasion and pleurectomy methods in patients with primary spontaneous pneumothorax undergoing a wedge resection for the bulleous part of the paranchyme. Materials and Methods: Statistically compared variables between the 2 groups were age, sex, symptoms, smoking status, number of previous pneumothorax episodes, surgical indication, bleb number, estimated blood loss, intraoperative complication, duration of the surgery, conversion to open surgery, postoperative drainage amount, chest tube removal time, length of hospital stay, morbidity, mortality, duration of narcotic analgesic usage, pain according to Visual Analog Scale evaluation, follow-up period, and postoperative recurrence. Results: The medical records of 88 patients undergoing surgery between 2013 and 2017 were reviewed retrospectively. The pleural abrasion group was superior to the pleurectomy group in terms of operation time, drainage volume, time to drain removal, hospital stay, and Visual Analog Scale pain score on postoperative day 0. Statistically, there was no difference between the pleural abrasion group and the pleurectomy group in the recurrence rates after operation (2.0% vs. 2.5%, respectively; P=0.89). Conclusions: Thoracoscopic pleural abrasion is safer than apical pleurectomy and is associated with the same pneumothorax recurrence rate.
Keywords: pleural abrasion; minimally invasive surgery; pleurectomy; pneumothorax; VATS; ASSISTED THORACOSCOPIC SURGERY; MECHANICAL PLEURODESIS; MANAGEMENT; THORACOTOMY; RECURRENCE